Methodical aspects of planning costs in management accounting and analysis - N. V. Puchkova (Путеводитель предпринимателя, 2020)
Planned and actual data about the level of costs of the organization are used to analyze the results of the execution of planned targets, determine the effectiveness of organizational and technical measures for the development of production of analytical calculations. The article describes the principles of planning costs, designated purpose of cost allocation, methodological aspects of planning expenditures under management accounting and analysis.